The Great War, 1914–18
XII, 195 p.
Keywords: The Great War is a collection of seven original essays and three critical comments by senior scholars dealing with the greatest conflict in modern history to its time - the 1914-18 World War. The Great War is edited by the distinguished historian of the First World War, R.J.Q.Adams.